'OPEN-EYED CONSPIRACY HIS TIME DOTH TAKE'. - Rundle, Guy (Overland)
An essay is presented on organization WikiLeaks and vanguardism in the information age. The author offers an overview of the organization which was initiated by Julian Assange. He discusses Assange's efforts of formulating ideas about challenging the consolidation of power, ideas related specifically to the flow of information facilitated by the spread of the internet. Also discussed are the legal suits filed by the U.S. government against the developer.